PENGUJIAN SIFAT MEKANIS BATAKO PEJAL DENGAN SERAT KELAPA DENGAN VARIASI 1,5 CM, 2 CM DAN 2,5 CM - ., Samsul; ., Herwani; Supriyadi, Asep (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
Brick is an infill material made from a mixture of cement, sand, with or without added ingredients and water. The amount of coconut fibers waste that has not been processed maximally the area of ​​Pontianak, West Kalimantan Province lead to an idea to use it as an ingredient in a mixture of brick. With theat consideration it will produce bricks that are addet material bricks, this research is purposed for that. The composition of the mixture used in this study are 1 pc: 6 ps with coconut fiber length variation of 1.5 cm, 2 cm and 2.5 cm of brick volume. Mixing done manually and moulding using solid brick mold dimension of 10 cm x 20 cm x 40 cm. Compressive strength testing is done at the time of the test specimen was 3, 7, 14 and 28 days. The test results showed that the addition of coconut fiber with fiber length of 2 cm and a percentage of fibers 10% of the volume of concrete brick, generating a maximum compressive strength of 4.210 MPa in comparison with other variations. The value increases in the ratio of compressive strength of concrete blocks over 17.389% of normal brick